Cyber Public Sphere and Social Movements Calling to Cyber Spaces - Çöteli, Sami (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
The diversification and politicisation of the mass media within itself and also societal pressure created by the mass media at a social level have caused changes to our social structure. The first change began with the contextual changes to the mass media, and this change led to visible changes in societies. That transformation has almost erased the distinction between the private and the public spheres, especially as social media has entered our lives. Now, things that occur in the private sphere are easily transported into the public sphere and others' private spheres. Therefore, the virtual public sphere has emerged through social media and all other practices on the internet. It appears that activist movements have either been founded in the cyberworld or that existing activist movements have been strengthened by finding supporters via social media and blogs. The public sphere and activist movements that come into existence in the virtual environment, such as social media, are a new experience in terms of societies, and they are the sign of how the future will be shaped. It is obvious that social media is now an integral part of our daily lives. It is a place where political and secular ideas spread. In this social area each individual has the opportunity to make political statements as if they were standing in an agora. Shared content represents the position within the virtual life that individuals have built for themselves. This study defines the virtual public sphere together with virtual activism and the network society in the light of the public sphere - private sphere debates.